2019
DOI: 10.1016/j.microrel.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

In-Operando X-ray diffraction imaging of thermal strains in fully packaged silicon devices

Abstract: The application of X-ray Diffraction Imaging to measure in operando thermal strains at individually powered components within fully packaged LM3046 silicon devices is described. It is shown that as the local strains increase with power dissipated, above a threshold power loading, the associated region of enhanced X-ray intensity increases monotonically. The changes in contrast in the image are discussed. Asterism in section topographs changes sign as the slit is moved across the component, consistent with latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…As reported in our previous paper (Tanner et al, 2019), the length of the direct image L D varied quadratically with power dissipated for all the devices measured. Though there was a substantial linear component to the curves, in all cases inclusion of the quadratic term was required to accommodate the measurement error bars.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…As reported in our previous paper (Tanner et al, 2019), the length of the direct image L D varied quadratically with power dissipated for all the devices measured. Though there was a substantial linear component to the curves, in all cases inclusion of the quadratic term was required to accommodate the measurement error bars.…”
Section: Resultssupporting
confidence: 74%
“…Crowding of the emitter-collector current results in heating towards the edge of the collector area, extending the hot spot as the power dissipated increases. [Although the increase in temperature counters the current crowding to some extent, as the temperature T is in kelvin, the change is estimated to be only a factor of two (Tanner et al, 2019)…”
Section: Figure 11mentioning
confidence: 99%
See 1 more Smart Citation
“…This fast and nondestructive method allows the tilt or strain measurement in operando as recently reported by Tanner et al [74] and could be also transferred from synchrotron to laboratorybased X-ray section mapping. [71]…”
Section: Quantitative Tilt Strain and Stress Measurementsmentioning
confidence: 77%
“…As a last example the fast and nondestructive metrology for packaged electronic devices will be given. The so called B-spline X-Ray diffraction imaging (B-XRDI) is proposed also for in operando studies by the group of McNally [69,70,71,72] and transferred to laboratory sources by Tanner et al [73,74] The strength of X-ray topography in material research will be demonstrated in the following by example of mainly electronic materials, which can be easily transferred to other crystalline materials too.…”
Section: Introductionmentioning
confidence: 99%